Terahertz wireless networking: principles, status and challenges - Tianhang ZHOU; Chuang YANG; Zile LIU; Mugen PENG; Li YU (Dianxin kexue, 2021)
To achieve huge capacity, terahertz communication has become an important technical option for 6G.Application and performance requirements of terahertz communication in typical indoor and outdoor scenarios were introduced emphatically.Then, based on the requirements of terahertz wireless networking, the research progress of key technologies such as topology design, media access control (MAC) layer protocol and neighbor discovery were summarized in detail.Last but not least, the challenges of terahertz wireless networking were discussed, and the possible future research directions were described.